Transparency and the KK Principle - Das, N; Salow, B (Wiley, 2016)
An important question in epistemology is whether the KK principle is true, i.e., whether an agent who knows that p is also thereby in a position to know that she knows that p. We explain how a “transparency” account of self‐knowledge, which maintains that we learn about our attitudes towards a proposition by reflecting not on ourselves but rather on that very proposition, supports an affirmative answer. In particular, we show that such an account allows us to reconcile a version of the KK principle with an “externalist” or “reliabilist” conception of knowledge commonly thought to make that principle particularly problematic.